Pengembangan Bahan Ajar IPAS Berbasis Kearifan Lokal Suku Mbojo pada Materi Indonesiaku Kaya Budaya Kelas IV di SDN Inpres Kaleo - Yuni Ros Meilasari; Muhammad Syazali; Hasnawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The use of local wisdom-based teaching materials is important to help students understand the material while fostering appreciation for regional culture. This study aims to develop and determine the validity, practicality, and effectiveness of science teaching materials based on the local wisdom of the Mbojo tribe on the topic My Indonesia is Rich in Culture for fourth-grade students at SDN Inpres Kaleo. The study employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation.The subjects consisted of 9 students in the limited trial, 1 teacher, and 14 students in the field trial. Data were collected through observation, interviews, expert validation questionnaires, practicality questionnaires, and tests, then analyzed using qualitative and quantitative approaches. The results showed validation scores of 95% from material experts and 89.29% from media experts, both categorized as very valid. Practicality was indicated by teacher responses of 97.92% and student responses of 93.61% and 92.68%, categorized as very practical. The N-gain score of 0.71 indicates high effectiveness. Thus, the teaching materials are very valid, practical, and effective. Teachers are encouraged to use them as references, students to use them optimally, and future researchers to develop  it with different cultures.